2002
DOI: 10.1002/1521-3765(20020104)8:1<208::aid-chem208>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Heterocyclic Cage Compounds by Domino Conjugate Additions

Abstract: Heterocyclic cage compounds have been stereoselectively synthesized from enantiopure [(S)R]-[(p-tolylsulfinyl)methyl]-p-quinols or their amine analogues and 2-(trimethylsilyloxy)furan in the presence of Bu4NF. The method is particularly valuable not only because of the stereochemical control but also because the reactions occur in an experimentally simple one-pot procedure through a domino sequence of three consecutive conjugate additions. The intermediate 1,4-adducts could be isolated when the reaction was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…152 Whereas unsubstituted quinols afford a 1:1 mixture of diastereoisomers, a methyl substituent on the double bond enables a complete diastereoselection. The resulting adducts were desulfinylated to produce enantiomerically pure cage compounds.…”
Section: Scheme 83mentioning
confidence: 99%
“…152 Whereas unsubstituted quinols afford a 1:1 mixture of diastereoisomers, a methyl substituent on the double bond enables a complete diastereoselection. The resulting adducts were desulfinylated to produce enantiomerically pure cage compounds.…”
Section: Scheme 83mentioning
confidence: 99%
“…We demonstrated that they are able to act as both acceptor and donor in successive conjugate additions. 8,9 Having in mind the reported biomimetic approaches to bisorbicillinoids and the interest of finding enantiopure and stable analogues of quinols, which could be used as substrates in biomimetic synthesis, we decided to explore if sulfinyl (1) Evidence supporting the real intermediacy of quinols in such biosynthetic routes has been recently reported: Abe, N.; Sugimoto, O.; Tanji, K.; Hirota, A. Jautelat, R.; Vassilikogiannakis, G.; Baran, P. S.; Simonsen, K. B. Chem. Eur.…”
mentioning
confidence: 99%
“…We demonstrated that they are able to act as both acceptor and donor in successive conjugate additions. 8,9 Having in mind the reported biomimetic approaches to bisorbicillinoids and the interest of finding enantiopure and stable analogues of quinols, which could be used as substrates in biomimetic synthesis, we decided to explore if sulfinyl p-quinol 1 and p-quinamine 2 could behave like the natural quinol metabolites in a dimerization process. It is known that free ortho-quinols, which are extremely reactive, dimerize instantaneously, 10 but there is not evidence of such behavior in p-quinols.…”
mentioning
confidence: 99%
See 2 more Smart Citations